2021
DOI: 10.3390/jcm10173957
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision versus Multiport Robotic Myomectomy: A Propensity Score Matched Analysis of Surgical Outcomes and Surgical Tips

Abstract: We aimed to compare the perioperative outcomes of single-incision robotic myomectomy (SIRM) and multiport robotic myomectomy (MPRM) and provide surgical tips. We retrospectively analyzed the medical records of 462 patients with symptomatic leiomyoma who underwent MPRM or SIRM between March 2019 and April 2021. Demographic characteristics and surgical outcomes, including the total operative time (OT), estimated blood loss (EBL), and surgical complication rate, were compared between the two groups. Patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…To the best of our knowledge, this is the first cohort study to have evaluated surgical outcomes of RSTM versus those of CRM. Although there have been two studies on RSTM [ 8 , 9 ], there is none that has weighed the pros and cons of RSTM against CRM’s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first cohort study to have evaluated surgical outcomes of RSTM versus those of CRM. Although there have been two studies on RSTM [ 8 , 9 ], there is none that has weighed the pros and cons of RSTM against CRM’s.…”
Section: Discussionmentioning
confidence: 99%
“…For CRM, four incision sites, including the 12-mm camera port at the umbilicus, two 8-mm side ports, and a 12-mm or 5-mm laparoscopic assistant port, are required. Robotic single-site myomectomy (RSSM) has been introduced to minimize surgical injury by reducing the number of ports; however, many studies have reported problematic issues due to inherent technical problems, such as limited traction with semi-rigid instruments, as well as range-of-motion limitations [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single-incision laparoscopic surgery is an important branch of laparoscopic technology that has been performed in almost every eld of surgery such as general surgery, gynecology, urology, and thoracic 4,5 . SILS offers potential bene ts over conventional laparoscopic surgery, including a reduced risk of trocar-related complications, reduced postoperative pain, and improved convalescence and cosmetic results [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…However, combining a challenging resection and multiple anastomoses is still a technical di culty. Single-incision laparoscopic surgery (SILS) has been widely used in gynecological and thoracic surgery with many bene ts including a reduced risk of trocar-related complications, reduced postoperative pain, and improved convalescence and cosmetic results 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested preferring abdominal or laparoscopic approach in cases with extreme myoma weight and abdominal in cases of large number of myomas. On the other hand, Kim et al [31] compared 30 robotic vs. 13 open surgeries for the removal of ≥ 10 myomas. Operating times were longer in the robotic approach (360 min vs. 180 min), while length of hospital stay was shorter (2.5 days vs. 3.5 days).…”
Section: Large/heavy/multiple Myomasmentioning
confidence: 99%